The Effect of Tax Planning, Leverage, and Profitability on Firm Value in the Consumer Goods Industry Sector Listed on the Stock Exchange Indonesia Year 2019-2023 - Mutiara Asriaty Nasution; Patar Marbun; H. Syahriandy (International Journal of Economic Research and Financial Accounting, 2024)
This study aims to determine the effect of Tax Planning, Leverage and Profitability on Company Value in the Consumer Goods Industry Sector Listed on the Indonesia Stock Exchange in 2019-2023. The population in this study is the Consumer Goods Industry Sector listed on the Indonesia Stock Exchange as many as 51 companies with a research period of 5 years (2019-2023) and obtained a research sample of 17 companies, using purposive sampling method. Based on the results of the t test, it can be seen that the t count on the Tax Planning variable is -1.774 < t table of 1.664 with a probability of t, namely sig 0.08> 0.05. Based on this value, the Tax Planning variable has no effect and is significant to the Company's Value. t test results can be seen that the t count on the Tax Planning variable is -1.774 < t table of 1.664 with a probability of t, namely sig 0.08> 0.05. Based on this value, the Tax Planning variable has no effect and is significant to the Company's Value. In the Leverage variable of -2.189 < 1.664 with a probability t, namely sig 0.03 < 0.05. Based on this value, the leverage variable has a negative and significant effect on firm value. On the profitability variable of 3.184> 1.664 with a probability t, namely sig 0.02 <0.05. Based on this value, the profitability variable has a positive and significant effect on firm value.